The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1080/16501970510032910
|View full text |Cite
|
Sign up to set email alerts
|

One-year follow-up of mild traumatic brain injury: Post-concussion symptoms, disabilities and life satisfaction in relation to serum levels of S-100B and neurone-specific enolase in acute phase

Abstract: In spite of frequent persistent symptoms, disabilities and low levels of life satisfaction, the sick-leave frequency was low at follow-up. The association between S-100B and disability supports the notion that long-term consequences of a mild brain injury may partly be a result of brain tissue injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 28 publications
2
76
2
Order By: Relevance
“…At least one fourth of the adults and the elderly patients gave signs of being under the influence of alcohol, which is the same fraction as reported by, for example, Nygren de Boussard et al (2004) and Stålnacke et al (2005). Our data is based on clinical signs, self-reporting and in some cases blood sample tests, making them minimum numbers.…”
Section: Epidemiology Of Brain Injuriessupporting
confidence: 50%
“…At least one fourth of the adults and the elderly patients gave signs of being under the influence of alcohol, which is the same fraction as reported by, for example, Nygren de Boussard et al (2004) and Stålnacke et al (2005). Our data is based on clinical signs, self-reporting and in some cases blood sample tests, making them minimum numbers.…”
Section: Epidemiology Of Brain Injuriessupporting
confidence: 50%
“…For example, Stalnacke et al (2005), using a blood biomarker of brain injury, serum concentrations of S-100B and neuron-specific enolase, found that S-100B levels during the acute phase of mTBI related to long-terms sequelae. S-100B findings have not been universal in mTBI (see also Bazarian et al, 2006a;Bazarian et al, 2006b;De Kruijk et al, 2002;Savola & Hillbom, 2003) and these observations are but some of the first.…”
Section: Pathophysiology Of Concussionmentioning
confidence: 99%
“…Thus, some refer to PCS if the symptoms persist for more than a few days and in particular, if the symptoms persist for more than a week Sheedy et al, 2006). If the symptoms last more than 3 months then the term persistent post-concussive syndrome or PPCS has been used (Begaz et al, 2006;Chamelian et al, 2004;Iverson, 2006;Rees, 2003;Satz et al, 1999;Stalnacke et al, 2005;Willer & Leddy, 2006). Whereas there is a relationship between severity of concussion and who develops PPCS (Hessen et al, 2006), concussion severity by itself is a poor predictor of who develops PPCS (Guskiewicz et al, 2004).…”
Section: Introduction: Brief History Of Concussionmentioning
confidence: 99%
“…Life satisfaction has been intensively studied in many patients groups encountered in rehabilitation medicine, especially patients with spinal cord injury [3,[10][11][12][13][14][15][16][17][18][19][20]. To our knowledge, however, it has scarcely been studied among patients with chronic pain [21][22][23].…”
Section: Introductionmentioning
confidence: 99%